ADHD symptoms impact smoking outcomes and withdrawal in response to Varenicline treatment for smoking cessation. (1st October 2017) - Bidwell, L. Cinnamon; Karoly, Hollis C.; Hutchison, Kent. E.; Bryan, Angela D.
Highlights: The role of Attention-deficit/hyperactivity disorder (ADHD) symptoms in a pharmacological smoking cessation trial is examined. Smoking cessation is associated with ADHD Hyperactivity/Impulsivity (HI) symptoms. Varenicline reduced smoking and withdrawal in individuals with high HI symptoms. Individuals with high HI symptoms in the placebo condition had the worst outcomes. Varenicline's effects may differ in individuals with high vs. low HI symptoms. Abstract: Introduction: Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with nicotine dependence and difficulty quitting smoking. Few cessation trials specifically consider the impact of ADHD on treatment outcomes, including those testing established pharmacological therapies, such as varenicline. Methods: The current study focused on the impact of pretreatment ADHD inattention (IN) and hyperactivity-impulsivity (HI) symptoms on treatment outcome in a randomized controlled trial of varenicline [N = 205, average age = 34.13( 10.07), average baseline cigarettes per day = 14.71( 7.06 )]. Given that varenicline's putative therapeutic mechanism is attenuation of withdrawal severity during abstinence, we also tested changes in withdrawal as a mediator of treatment effects in high and low ADHD groups. Results: ADHD symptom severity in this sample was in the subclinical range. Cessation was associated with HI, but not IN, such that high HI individuals on varenicline reported the lowest smoking levels at the end of treatment across all groups (3.06 cig/day for high HI vs 4.02 cig/day for low HI). Individuals with high HI who received placebo had the highest smoking at the end of treatment (7.69 cigs/day for high HI vs 5.56 cig/day for low HI). Patterns continued at follow-up. Varenicline significantly reduced withdrawal for those with high HI, but not low HI. However, path models did not support an indirect effect of medication on reducing smoking via withdrawal in either group, suggesting that unmeasured variables are involved in varenicline's effect on reducing smoking. Conclusions: These data add to a gap in the smoking cessation literature regarding the impact of ADHD symptoms on the efficacy and mechanisms of frontline pharmacological treatments.